Insulin metabolism markers are predictors of subclinical atherosclerosis among overweight and obese children and adolescents - Asghari, Golaleh (BMC Pediatr, 2018)
BACKGROUND: To investigate the association between markers of insulin metabolism and carotid intima-media thickness(cIMT) among overweight and obese children and adolescents. METHODS: A total of 378 children and adolescents aged from 6 to 13 years, with WHO body mass index Z-Scores ≥2 were enrolled in this study. We measured fasting serum insulin and glucose, conducted a homeostatic model assessment of insulin resistance(HOMA-IR), and calculated the quantitative insulin sensitivity check index(QUICKI). Carotid intima-media thickness was measured in the common carotid artery with high-resolution ultrasonography. RESULTS: The study participants consisted of 198 boys and 180 girls with a mean(±SD) age of 9.3 ± 1.7 years, 18.3% being pre-pubertal. In boys, after controlling for confounders, a one-SD increase in fasting insulin and HOMA-IR were associated with 0.351 mm(P < 0.001) and 0.350 mm(P < 0.001) increases in cIMT, respectively. However, a one-SD increase in QUICKI was associated with a − 0.305 mm(P = 0.001) decrease in cIMT. When categorizing into tertiles, a one-SD increase in fasting insulin and HOMA-IR were associated with 87 and 81% increases in the odds of higher categories of cIMT(both P < 0.05). However, a one-SD increase in QUICKI was associated with 37% lower odds of higher categories of cIMT(P = 0.022). No significant associations were found among girls. CONCLUSION: This study demonstrated that insulin resistance and sensitivity markers were independent predictors of cIMT in overweight and obese boys, but not in girls, highlighting the importance of chronically elevated insulin levels for predisposing these boys to alterations in their vascular structure.